Experimental study on the combustion and emission characteristics of thermal storage-assisted load reduction in a circulating fluidized bed - Zengcai Ji; Guoliang Song; Haiyang Wang (Fuel Processing Technology)
As a critical component of coal-fired power systems, circulating fluidized bed (CFB) boilers play a pivotal role as flexible power sources in modern power grids, contributing to grid reliability and operational stability. To address the challenges of significant thermal inertia and low load reduction rates inherent in CFB boilers, this study conducts experimental investigations into the combustion and emission characteristics during thermal storage-assisted load reduction. The results indicate that the thermal storage-assisted load reduction method can effectively improve the boiler's load regulation performance. However, the rate of load reduction varies significantly across different load ranges: when reducing from 100 % to 50 %, 100 % to 30 %, and 50 % to 30 %, the rates increased by 23 % and 9 %, and decreased by 62 %, respectively. Compared with the conventional load reduction method, thermal storage-assisted operation slightly improves combustion efficiency, increases NOx emissions, and reduces CO emissions. Increasing the amount of stored heat significantly alters the furnace temperature distribution - larger temperature drops in the lower region and smaller drops in the upper region - accompanied by higher NOx emissions, lower CO emissions, improved combustion efficiency and improved load reduction rate. When reducing load from 100 % to 50 %, increasing the stored material to 14 %, 24 %, and 34 % led to corresponding load reduction rate improvements of 18 %, 23 %, and 111 %, respectively.